KONVEKSITAS, KEHALUSAN, DAN PEMETAAN DUALITAS - , ROMADZON SYAIFUL HAQ ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project we discuss about some geometric properties of a Banach space. First we discuss about convexity of a Banach space such as strict convexity, uniform convexity, and modulus of convexity. We continue by discussing about duality mappings. In the discussion of the duality mappings we also discusses subdifferential of proper convex functions and the relation of subdifferential with duality mappings. Finally we discuss about smoothness of Banach spaces.